Early predictors for mechanical ventilation in COVID-19 patients. (October 2020) - Li, Wen; Lin, Fengyu; Dai, Minhui; Chen, Lingli; Han, Duoduo; Cui, Yanhui; Pan, Pinhua
Objective: To identify potential predictors for invasive and non-invasive mechanical ventilation in coronavirus disease 2019 (COVID-19) patients. Methods: This study retrospectively analyzes data of 516 patients with confirmed COVID-19, who were categorized into three groups based on which mechanical ventilation method was used during the hospitalization period. Results: Among 516 confirmed cases with COVID-19, 446 patients did not receive mechanical ventilation, 38 patients received invasive mechanical ventilation (IMV) and 32 received non-invasive mechanical ventilation (NIMV). The median age of the included patients was 61 years old (interquartile range, 52–69). A total of 432 patients had one or more coexisting illnesses. The main clinical symptoms included fever (79.46%), dry cough (66.47%) and shortness of breath (46.90%). IMV and NIMV patients included more men, more coexisting illnesses and received more medication. Patients in the IMV group and NIMV had higher leukocyte and neutrophil count, lower lymphocyte count, higher aspartate aminotransferase (AST), lactate dehydrogenase (LDH), C-reactive protein (CRP), procalcitonin (PCT) and D-dimer levels and lower albumin (ALB) level. The univariate and multiple logistic regression analysis showed that the use of glucocorticoid, increased neutrophil count and LDH had a predictive role as indicators for IMV, and the use of glucocorticoid, increased neutrophil count and PCT had a predictive role as indicators for NIMV. The area under the curve (AUC) of use of glucocorticoid, increased neutrophil count and LDH was 0.885 (95% confidence interval (CI) 0.838–0.933, p < 0.0001), which provided the specificity and sensitivity 77.7% and 90.9%, respectively. AUC of the use of glucocorticoid, increased neutrophil count and PCT for NIMV was 0.888 (95% CI 0.825–0.952, p < 0.0001), which provided the specificity and sensitivity 70.3% and 96.4%, respectively. Conclusion: Glucocorticoid, increased neutrophil and LDH were predictive indicators for IMV, whereas glucocorticoid, increased neutrophil and PCT were predictive indicators for NIMV. In addition, the above-mentioned mediators had the most predictive meaning for mechanical ventilation when combined. The reviews of this paper are available via the supplemental material section.